Some Properties of a subclass of Harmonic Univalent Functions defined by fractional calculus: Saurabh Porwal - Team, Support (Thai Journal of Mathematics, 2015)
The purpose of the present paper is to a systematic study of a new class of harmonic univalent functions defined by fractional calculus operator. Apart from coefficient bound, extreme points and distortion theorem, many interesting and useful properties of this class of functions is given, some of these properties concerning fractional calculus, convolution, partial sums and neighborhoods are also indicated. It is worth mentioning that results obtained in 12 appear to be particular cases are of our results. Many of our results are quite new and improves the results of previous authors and not found in the literature so far.